The Muallaqat of Imru' al-Qays: The Lost Kingdom and the Alternative Victory - Abbas , Ass. Prof. Dr. Haider Fadel (Thi Qar Arts Journal, 2022)
The Muallaqat are the most famous of the pre-Islamic poetry that reached us, the most versed, the most complete in structure, and the farthest in impact. These muallaqat that we inherited from the pre-Islamic era were not without precedent. Rather, they are a mature end to the initial attempts that preceded and led to them. Poetry in its purest form. It exceeded the scope of admiration and imitation until it became a present text - even if it was absent - in the Code of Arab Poetry. And her poets won this prestige among their peers among the poets of the pre-Islamic era, and Imru’ al-Qais’ commentary is the mediator of the contract, as its owner was the first of the first class among all scholars and critics of Arabic poetry.Imru' al-Qays's mu'allaqa has accomplished itself outside the limits of time and space, and within the circle of eternity, as it is the genius that keeps its secret.The apparent structure of Imru’ al-Qais tells that it does not address a specific topic, but rather its verses are distributed in different scenes: the scene of ruins, the scene of storytelling, the scene of the night of tragedy, the scene of the horse, and the scene of rain and torrential rain. However, critical reflection on its inner worlds reveals that these scenes, despite their plurality, lead to their deep structure, which is concentrated in the poet's defense of his grieving self, due to the loss of his possession and that of his father. Therefore, his flirtatious pride and extraordinary chivalry were his alternative victory, so that the end of the battle remains suspended between the vanquished reality and the victorious imagination.